Combustion mechanism and control approaches of underground coal fires: a review - Liang, Yuntao; Yang, Yalan; Guo, Sida; Tian, Fuchao; Wang, Shaofeng (International journal of coal science & technology, 2023)
With the large-scale mining of coal resources, the huge economic losses and environmental problems caused by underground coal fires have become increasingly prominent, and the research on the status quo and response strategies of underground coal fires is of great significance to accelerate the green prevention and control of coal fires, energy conservation and emission reduction. In this paper, we summarized and sorted out the research status of underground coal fires, focused on the theoretical and technical issues such as underground coal fire combustion mechanism, multiphysics coupling effect of coal fire combustion, fire prevention and extinguishing technology for underground coal fires, and beneficial utilization technology, and described the latest research progress of the prevention and control for underground coal fire hazards. Finally, the key research problems in the field of underground coal fire hazards prevention and control were proposed in the direction of the basic theory, technology research, comprehensive management and utilization, with a view to providing ideas and solutions for the management of underground coal fires.